Who runs the fastest? Anthropometric and physiological correlates of 20 m sprint performance in male soccer players. Issue 4 (1st October 2016) - Nikolaidis, P. T.; Ruano, M. A. G.; de Oliveira, N. C.; Portes, L. A.; Freiwald, J.; Leprêtre, P. M.; Knechtle, B.
ABSTRACT: The aim of the present study was to examine the relationship of 20 m sprint performance with anthropometrical and physiological parameters in male soccer players. A hundred and 81 soccer players from the region of Athens (age 23.4 ± 5.0 yrs, body mass 73.4 ± 7.7 kg, height 180.0 ± 5.9 cm, body fat (BF) 14.4 ± 3.6%), classified into quartiles according to 20 m sprint time (group A, 2.84–3.03 s; group B, 3.04–3.09 s; group C, 3.10–3.18 s; group D, 3.19–3.61 s), participated. Soccer players in group A were younger and had better performance in vertical jumps and in the Wingate anaerobic test (WAnT, p < 0.05). Sprint time correlated to age ( r = 0.27), body mass ( r = 0.23), body height ( r = 0.20), BF ( r = 0.23), vertical jumps (−0.58 ≤ r ≤ −0.50) and the WAnT (−0.45 ≤ r ≤ −0.30, p < 0.05). In summary, the magnitude of correlations of sprint time with measures of lower limbs muscle strength and power (WAnT and jumps) was larger than with anthropometric measures (body mass and BF).